(untitled) (IAHS Medical Journal, 2024)
Background: Fever is the most common cause of convulsions, in infancy and childhood. Complex febrile seizures are associated with an increased risk of subsequent epilepsy. The present study aimed to evaluate the role of serum sodium levels and associated factors in children with simple and complex febrile seizures admitted to a tertiary level hospital in Bangladesh. Materials and methods: Children aged between 6 months to 60 months with febrile seizures, admitted to the Paediatric ward of Chittagong Medical College Hospital, Chattogram, were recruited in the study. Serum sodium level at admission were estimated and patients were categorized into two group: simple and complex febrile seizure. Data were analyzed by comparing different variables between two groups. Results: A total of 60 children were enrolled in the study in which 36 were diagnosed with simple febrile seizures and 24 of them with complex febrile seizures. The mean age was 22.3 months and there was male preponderance with a male to female ratio of 2.3:1. The mean serum sodium level was 136.9±6.5 mmol/l and 18 (30%) patients had hyponatremia. Serum sodium levels were significantly lower in children with complex febrile seizure (134.0±6.1 and 138.9 ± 6.0, p=0.003) than the children with simple seizure. The optimal cutoff value of serum sodium level was 134 mmol/L with an area under the receiver operating characteristic curve of 0.723 (95% CI: 0.590-0.856), with sensitivity of 80.0% and specificity of 50.0%. Conclusions: Our study suggested that serum sodium levels were significantly lower in children with complex febrile seizures. However, because of its lower specificity value, further studies are needed to confirm the utility of serum sodium level in childhood febrile seizure. IAHS Medical Journal Volume 6(1) June 2023; 34-38